QUALITY CONTROL ASSESSMENT OF DUTASTERIDE AND SILODOSIN IN CAPSULES AND TABLETS EMPLOYING A NOVEL DEVELOPED HPLC TECHNIQUE; EVALUATION OF STABILITIES OF DUTASTERIDE AND SILODOSIN IN ACCELERATED DEGRADATION - JAGADEESH, KADALI; KADIYALA, K. GANESH; VARMA DENDUKURI, B. N. SURESH; GUTTULA, RAMA SWAMY; GUPTA TIRUVEEDHI, V. L. N. BALAJI; VAMSI, PEDDINTI; CHAVAKULA, RAJYA LAKSHMI (International Journal of Applied Pharmaceutics, 2023)
Objective: The combination of dutasteride (DTRE) plus silodosin (SLDN) is used for treating acute urine retention brought upon by benign prostatic hyperplasia in men. The contents of DTRE and SLDN in capsules and tablets must be monitored for quality. In this research, a quick, selective and robust stability indicating HPLC method has been developed for concurrent assay of DTRE and SLDN in capsules and tablets. Also, the stabilities of DTRE and SLDN under several types of applied stress were determined. Methods: Analysis performed using Xterra Symmetry type column C18 (“4.6 mm x 150 mm, 5 mm” dimensions) and mobile phase having 0.1N strength, 20% volume fraction of dipotassium hydrogen phosphate and 80% volume fraction of pure form acetonitrile; PDA analysis was made at 265 nm. Stabilities of DTRE and SLDN were determined under several types of applied stress, including thermal, basic, oxidative, photo, and acid. Results: The elution times for DTRE and SLDN were 2.003 min and 3.377 min, respectively. DTRE and SLDN linear ranges were 20–120 µg/mL and 1.25–7.5 µg/mL, respectively. Method is precise with 0.2498% (DTRE) and 0.0773% (SLDN) RSD values. Method is accurate with 98.913-101.049% (DTRE) and 100.023-100.162% (SLDN) recovery values. In degradation investigation, degradant’s peaks elution times are different from the elution times of DTRE and SLDN. Thus, proved specificity and stability indicating power of the method. DTRE and SLDN were found relatively stable in thermal and were found sensitive in oxidation. In overall, SLDN found more sensitive to applied stress, including thermal, basic, oxidative, photo, and acid compared to DTRE. Conclusion: Finally, this developed analytical approach was efficaciously applied to a commercial capsule and tablet formulations containing fixed dose of DTRE and SLDN, demonstrating its usefulness for quality control and degradation investigations on DTRE and SLDN.